Pakaian Pernikahan Rakyat dalam Naskah Platenalbum Yogyakarta No. 26-30 - Ma'rufah, Hafidhoh; Rahma, Awalia (Perpustakaan Nasional Republik Indonesia, 2025)
The Yogyakarta Platenalbum manuscript is a manuscript that tells about Javanese culture, especially Yogyakarta. This text contains various cultures, such as children's games, palaces, people's weddings, ceremonies inside and outside the court, tales, wayang, performances, procedures, customs, agriculture, and one text that explains Candraning Wanita. Using literature library research, this article discusses people's wedding attire in the Yogyakarta Platenalbum manuscript No. 26-30. From this research process, several models of clothing were used during commoners' wedding celebrations. The clothes worn by the people are certainly different from those used by the royal family. This is caused by differences in social status in Javanese society, especially in Yogyakarta and Surakarta. In different moments or processions, but still in a series of weddings, the bride and groom wear different clothes. Not only the bride and groom, but the family and neighbors involved in a series of wedding rituals, also wear clothes regulated by Javanese custom.